2011
DOI: 10.1002/jcb.23209
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin induces cell migration through GHS-R, CaMKII, AMPK, and NF-κB signaling pathway in glioma cells

Abstract: Ghrelin is a newly discovered gastric peptide which stimulates food intake, energy balance, and growth hormone release. Recent reports have also shown that circulating ghrelin can efficiently reach the brain. However, the molecular mechanisms and pathophysiologic roles underlying ghrelin-induced glioma migration remain unclear. Glioma is the most common primary adult brain tumor with poor prognosis because of the spreading of tumor cell to the other regions of brain easily. In present study, we found that appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 77 publications
4
48
0
Order By: Relevance
“…involved in cell motility (Dixit et al 2006, Chen et al 2011. In our study, we observed GHR and GRLN-R1a immunolabelling in astrocytes of the hypothalamic arcuate nucleus and of the dentate gyrus in the hippocampus.…”
Section: Discussionsupporting
confidence: 65%
“…involved in cell motility (Dixit et al 2006, Chen et al 2011. In our study, we observed GHR and GRLN-R1a immunolabelling in astrocytes of the hypothalamic arcuate nucleus and of the dentate gyrus in the hippocampus.…”
Section: Discussionsupporting
confidence: 65%
“…2010) and CaMKII activation in glial cells (Chen et al. 2011). To our knowledge, we are the first to report AG‐induced phosphorylation of CaMKII in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The ghrelin receptor is also present in astrocytomas, with astrocytoma cell lines expressing higher levels of GHSR1a compared with primary cultures of normal astrocytes [92,93]. Ghrelin promotes cell motility in astrocytomas and, given that it is a positive regulator of the somatotropic axis, it could play a role in astrocytoma cell growth and function with an endogenous hormonal loop, critical in astrocytoma motility and invasiveness, possibly being involved [93].…”
Section: Ghrelin Receptors In Astrocytesmentioning
confidence: 99%